2019
DOI: 10.1126/scitranslmed.aau8217
|View full text |Cite
|
Sign up to set email alerts
|

Treating murine inflammatory diseases with an anti-erythrocyte antibody

Abstract: Treatment of autoimmune and inflammatory diseases typically involves immune suppression. In an opposite strategy, we show that administration of the highly inflammatory erythrocyte-specific antibody Ter119 into mice remodels the monocyte cellular landscape, leading to resolution of inflammatory disease. Ter119 with intact Fc function was unexpectedly therapeutic in the K/BxN serum transfer model of arthritis. Similarly, it rapidly reversed clinical disease progression in collagen antibody-induced arthritis (CA… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 18 publications
(15 citation statements)
references
References 80 publications
0
15
0
Order By: Relevance
“…In effect, by 10 days the affected joints are extensively damaged and inflammation subsides thereafter. Inflammation can be maintained by repeated serum transfers, but there is no evidence of additional joint destruction (63)(64)(65).…”
Section: A B Cmentioning
confidence: 99%
“…In effect, by 10 days the affected joints are extensively damaged and inflammation subsides thereafter. Inflammation can be maintained by repeated serum transfers, but there is no evidence of additional joint destruction (63)(64)(65).…”
Section: A B Cmentioning
confidence: 99%
“…Arachidonic acid metabolism pathway was demonstrated to be relate with mechanism of tocilizumab in dealing with early RA patients [ 24 ]. Adherens junction is indispensable components of the vessel wall that affect vascular permeability [ 25 ] while activation of complement and coagulation cascades modulates synovium and systemic inflammation [ 26 ]. The enrichment results suggested that function of YQCP is closely associated with RA therapy.…”
Section: Resultsmentioning
confidence: 99%
“…21 This conclusion is also supported by studies evaluating polyclonal anti-D, where responses did not correlate with erythrocyte-sensitization, hemolysis, hemoglobin, or haptoglobin levels. 6,9,10,18,19,22 We have previously shown that TER119 ameliorates ITP before signs of anemia and does not have a therapeutic effect concordant with maximal anemia, 15 indicating that anemia itself may be uncoupled from therapeutic activity. In the present work, 3 antibodies (deglycosylated TER119, CBC512, and MIMA29) induced anemia but failed to ameliorate murine ITP, suggesting that anemia itself is insufficient to ameliorate ITP by antierythrocyte antibodies.…”
Section: Resultsmentioning
confidence: 99%
“…9,10 To add to the complexity, we have recently shown that the TER119 antibody, which mimics the action of anti-D in murine ITP amelioration, [12][13][14] has anti-inflammatory effects in murine arthritis and can prevent disease activity in a murine model of transfusionrelated acute lung injury. 15 Since the spleen and the MPS are not a priori involved in the development of arthritis or transfusion-related acute lung injury, this could question the simplistic concept of MPS blockade in the therapeutic action of anti-erythrocyte antibodies.…”
Section: Introductionmentioning
confidence: 99%